The Influence of Work Discipline and Employee Retention on Employee Performance: Evidence from PT UGS - Wahyuningtyas, Ratri; Rifqi, Bayu Tinarta (Eastasouth Institute, 2025)
This study investigates the effect of work discipline and employee retention on employee performance at PT UGS, a technology-based service company operating in the marine sector. Employing a quantitative approach with a causal research design, data were gathered through a structured questionnaire distributed to all 94 employees using a total sampling method. The research instruments underwent tests for validity and reliability, followed by classical assumption testing including normality, multicollinearity, and heteroscedasticity. The results indicate that both work discipline and employee retention have a positive influence on employee performance, both individually and collectively. Employees who consistently adhere to workplace standards and show long-term commitment tend to perform better. These findings underscore the importance of promoting discipline and fostering loyalty as strategic efforts to enhance organizational productivity. This study contributes to the field of human resource management by highlighting the significance of behavioral consistency and employee engagement in optimizing workforce performance, offering valuable input for HR policy development.